How to be human - Amira Azmi (2018)
‘How To Be Human’ presents a fictional setting where our autonomy and individuality are completely nonexistent. Via a satirical lens, the project criticises our desperate need for clarity in a chaotic world, which Albert Camus referred to as ‘The Absurd’. In this fictional setting, humans are each assigned a package containing all the information about their lives including when they will die, their career path, traits and preferences. The project will also give a peek into what a manual on how to be human would look like, highlighting four principles that require human beings to be: 1) Mechanical, 2) Rational, 3) Static and 4) Compliant. The project invites the audience to reflect on our habit of conformity, ridiculous social conventions and our slow descent into a completely mechanical human life. When provided with information on everything about your life, would you feel relieved by the lack of ambiguity or would you instead have a greater appreciation of your personal freedom?